El impacto en la motivación laboral de los colaboradores administrativos del área de operaciones comerciales de la empresa Luz del Sur durante pandemia del COVID 19 - Alcalde Chumbiray, Carla Sofia (2022)
The objective of this research is to analyze the impact on the work motivation of theadministrative collaborators of the commercial operations area of the company Luz del Sur during the COVID 19 pandemic. In order to confirm this hypothesis, we have based ourselves on relating Maslow’s Pyramid Theory with the needs that the administrative collaborators have. For data collection, we elaborated a survey that was applied to 81 people, who are the administrative collaborators of the commercial operations area of the company Luz del Sur and the questions are related to each need of Maslow’s Pyramid Theory. To analyze the answers of the questionnaire, the SPSS vs27 (2021) program was used.Finally, the results show that the pandemic did affect the needs of the workers (Maslow's Pyramid Theory).